Adapting agile workflows to accelerate geoscience study results. Issue 1 (1st December 2019) - Philip, Lendyn
Summary: Woodside Exploration routinely conducts large regional study projects to inform business decisions regarding new acreage, data acquisition and drilling. Whilst varied, these studies generically comprise phases of data collection and conditioning, analysis, collaboration and actions leading to assurance and finally completion. These studies are usually managed in a linear, or Waterfall, approach and time taken to complete these phases ranges from weeks to months depending upon complexity. An 'Agile' approach, originally developed for rapid software development, has been modified to fit geoscience studies insofar as we define a 'Rapid Study Sprint' (RSS) that combines the analysis and collaboration phases of the project into a facilitated workshop, at the end of which preliminary products must be completed. The RSS is analogous to a hackathon and leverages intense collaboration to drive fit-for-purpose outcomes. Woodside Exploration Australia held its first RSS in 2017 to produce a play-based exploration evaluation of the Jurassic (J50) Macedon play interval in the Exmouth Sub-basin, offshore Western Australia. In one day of intense collaboration, the RSS generated maps of equivalent quality to traditional regional studies. This paper compares the actual time and cost of this RSS with a notional project plan for a conventional regional study with the same objectives and deliverables. Comparison demonstrates that the RSS and conventional regional project has a similar ultimate duration. However, the distribution of effort and reward varies considerably; with a 40% cost saving attributed to the reduction in worked hours and delivery of usable products two weeks earlier. Savings are attributed to the core principles of Agile driving collaborative behaviours and simplifying business processes to focus effort on the highest priority areas to address the key project objectives.